Spatial and Temporal Variations of Freezing and Thawing Indices From 1960 to 2020 in Mongolia - Dashtseren, Avirmed; Temuujin, Khurelbaatar; Westermann, Sebastian; Batbold, Altangerel; Amarbayasgalan, Yondon; Battogtokh, Dorjgotov (Frontiers in Earth Science, 2021)
Mongolia is one of the most sensitive regions to climate change, located in the transition of several natural and permafrost zones. Long-term trends in air freezing and thawing indices can therefore enhance our understanding of climate change. This study focuses on changes of the spatiotemporal patterns in air freezing and thawing indices over Mongolia from 1960 to now, using observations at 30 meteorological stations. Our results shows that the freezing index ranges from -945.5oC day to -4793.6oC day, while the thawing index ranges from 1164.4oC day to 4021.3oC day over Mongolia, and their spatial patterns clearly link to the latitude and altitude. During the study period, the trend in the thawing index (up to 14.4°C-day per year) was larger than the trend in the freezing index (up to -10.1°C-day per year). Overall, the increase in the thawing index was larger in the low latitudes and altitudes (e.g., the Gobi-desert, steppes, the Great lake depression and major river valleys) than in high latitudes and altitudes (mountain regions), while it was the opposite for the freezing index. The highest values for both thawing index and freezing index (i.e. the least negative values) have occurred during the last two decades. As the trends in the freezing and thawing indices confirm climate warming, increased permafrost degradation and shallower seasonally frozen ground are expected throughout Mongolia.